Desarrollo de una aplicación móvil para la compra y venta de vehículos de la empresa Riomotor Innovation - Guacho Bastidas, Jhon David (2025)
The present curricular integration project aimed to develop a mobile application to streamline the buying and selling of new and used vehicles for the company RIOMOTOR INNOVATION, providing an efficient and secure solution. The Scrum methodology was applied to ensure an agile approach that suited the project’s needs throughout its stages. In the planning phase, requirements were collected through interviews, identifying the app’s specifications based on the IEEE-830 standard. During the design stage, architectural models such as software structures and diagrams were created using Lucidchart. For coding, the designs were transformed into source code using NodeJS and Express for the backend, and Flutter for the frontend, with MongoDB selected as the database manager. In the testing phase, functions and widget integration were verified for proper implementation. Finally, during the deployment phase, the necessary configurations were completed for publishing the app on the Google Play Store. The implementation of the application has had a positive impact on RIOMOTOR INNOVATION by optimizing interactions between the company and its clients. Thanks to this tool, the company has streamlined its commercial processes, improved user experience, and expanded its reach in the digital market, which potentially increases business opportunities and customer loyalty.